Impact of Scleroderma‐Associated Autoantibodies on Clinical Outcome Assessments: Post Hoc Analysis From a Randomised, Double‐blind, Placebo‐controlled, Phase 3 Trial of Tocilizumab in Scleroderma - Basmah Al Dulaijan; Suiyuan Huang; Celia J. F. Lin; Christopher P. Denton; Dinesh Khanna (ACR Open Rheumatology)
Objective Scleroderma‐associated autoantibodies (SSc‐Abs) are specific in participants (pts) with systemic sclerosis and are associated with organ involvement. Our objective was to assess the influence of baseline SSc‐Abs on the trajectories of the clinical outcome assessments (COAs) in a phase III randomized controlled trial. Methods We used data on both the groups who received placebo (Pbo) and tocilizumab from the focuSSced trial. The SSc‐Ab panel was assessed centrally. We analyzed four groups with SSc‐Abs: anti–topoisomerase 1 antibody (ATA), anti–RNA polymerase 3 antibody (RNAP3), anti‐centromere antibody, and negative for all three (triple negative). We assessed the impact of baseline SSc‐Abs on six COAs: modified Rodnan skin score (mRSS), forced vital capacity (FVC%), Health Assessment Questionnaire Disability Index, patient and clinical global assessments, and American College of Rheumatology (ACR) Composite Response Index in Systemic Sclerosis (CRISS). Results We observed that all COAs, except for FVC%, improved for the group who received Pbo during the 48‐week period. For mRSS, pts with RNAP3 showed the largest Pbo effect (7.20 per year, n = 14) and smallest for ATA (3.28 per year, n = 49). This trend was also seen for the ACR CRISS (0.00–1.00 scale), with median improvement at week 48 of 0.94 for RNAP3 versus 0.01 for ATA. ATA enriched for FVC% decline of 7.34% per year versus 2.54% per year for RNAP3. In the group who received tocilizumab, similar changes were seen in the mRSS and ACR CRISS with preservation of lung function, irrespective of SSc‐Ab type. Conclusion Our result shows a differential effect of SSc‐Abs on the trajectories of COAs over 48 weeks in group who received Pbo. These findings highlight the importance of incorporating SSc‐Abs in trial design, either as a stratification factor or limiting the SSc‐Abs that are included in the trials.